Eponyms from Mustafa: A Morphosemantic Analysis - Riaz, Muhammad; Mangrio, Riaz Ahmad (Pakistan Languages and Humanities Review, 2023)
Mustafa is the personal name of the Holy Prophet Hazrat Muhammad (SAW). This name has religious sanctity for the Muslims all over the world. The Muslims feel elated in showing their affiliations with this name by using eponyms derived from it. An eponym is actually a name derived from some personal name of a person, place or mythical character. The name derived from the personal name of a person is called anthroponymic eponym. The name Mustafa is highly productive anthroponym in the sense that it presents its various eponymous formations which the present research aims to explore through the application of Distributed Morphology (DM). The researcher has delimited his research only to the morphosemantic nuances of the single name [Mustafa]. Distributed Morphology is a new and emerging theoretical framework which helps to find lexical meanings through syntactic and morphological operations . We find few of its applications on morphology and semantics in general but there us rare one is on religious names and particularly on Mustafa. The research discovers the productivity and richness of the particular name showing that Islamic names are highly productive morphologically as well as semantically. This research may help to analyse religious names from socio-cultural perspectives also.